SPELLING ERROR FOUND ON DESCRIPTIVE TEXT IN EIGHTH GRADE STUDENTS OF SMPN 18 MALANG - ISWARA, DONI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Writing, descriptive text, spelling error, junior high school students Sometimes it is not easy for learners of English to write a text since this skill requires several aspects that should be noticed such as grammatical structure, organization of idea, and the spelling. In this research, the researcher focused his concern in spelling. Spelling the word correctly is important in writing and it can be a serious attention for beginner learners of English such junior high school students. This research was intended to investigate the type of spelling errors made by eighth grade students of SMPN 18 Malang and to figure out the most type of spelling errors committed by the students by using a descriptive text as a medium to gain the spelling error words.In conducting the research, the researcher asked the students to write a descriptive text. In analyzing the data the researcher used formal errors of lexis theory that proposed by James (1998) especially the taxonomy of distortion type to identify the type of spelling errors. The data were 52 spelling errors which were taken from 26 descriptive texts.The researcher revealed that the spelling errors occurred in the the subtypes of omission, overinclusion, misselection, and misordering. The researcher also found that the most occurred spelling error are in the sub-types of omission and misselection. Both types share the same percentage which is 39% for each. From the results that were found, the researcher concluded that the students actually know about the intention of using the vocabularies but they were still lack in applying those words especially in its written form. In other words, they are familiar with the pronunciation of the words but they are careless in writing the words using correct spelling.To solve that problem, the researcher suggests for the students to improve their vocabulary and spelling knowledge not only in the classroom activity but in others productive activities such reading a material in English. For the teacher, the researcher suggests to take more attention on spelling by creating an activity that can improve the spelling skill. For the future researchers, it is better to conduct the research in different object such as movie subtitle or in oral spelling.